Using a Health Equity Lens to Evaluate Short-Term Experiences in Global Health (STEGH). Issue 1 (11th November 2020) - Tsang, Vivian W. L.; Loh, Lawrence
Background: The growing popularity of short-term experiences in global health (STEGH) has given rise to increasing criticism around their purported benefits and outcomes. With the global health and development community's growing focus on improving population health and equity worldwide as outlined in the United Nation's Sustainable Development Goals, there is a growing opportunity to examine and optimize the conduct of STEGH using an outcomes and equity focused lens. Objectives: This viewpoint aims to develop a framework that can be used to plan and evaluate STEGH on outcomes underpinned by a health equity focus. Methods: Drawing on logic model theory, the analysis first identifies extant issues and their drivers around the planning, implementation, and evaluation of tradition STEGH (focused on clinical service provision.) The analysis then explores various definitions of health equity, settling on a broad definition around context that promotes health for all as opposed to equity of access to healthcare services. With that definition as the ultimate benchmark of success, the analysis then proposes questions that can be used to determine how and when a STEGH might best be deployed to meet that goal. Findings: Traditional reliance on process outputs from service-based approaches have historically limited an understanding of if and how STEGH might advance health equity. Using an outcomes-focused approach identifies critical questions around the value of such experiences, when weighed against a broad definition of equity and other key global health themes such as sustainability, cultural humility, and impact. Measuring STEGH against the goal of improving population health status and equity worldwide allows careful consideration of the appropriateness and effectiveness of such efforts on their own and in concert with other interventions. Conclusions: The extent to which health equity is advanced should be the ultimate metric used to evaluate not only STEGH, but any global health endeavours.